2013
DOI: 10.1016/j.thromres.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Whole Blood Clot Strength Measured by Thrombelastography in Patients Treated with Clopidogrel during Acute Coronary Syndromes

Abstract: Introduction Treatment with clopidogrel, a selective platelet P2Y12 receptor antagonist, reduces risk of recurrent ischemic events in patients with acute coronary syndrome (ACS), by limiting platelet aggregation and activation. Stable whole blood clot formation requires activation of platelets, generation of fibrin and final fibrin crosslinks. In this study we intended to compare plasma and whole blood thrombelastography (TEG) measurements in patients during ACS. Materials and Methods Whole blood and plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…Thus, variability in platelet derived FXIIIa may contribute to differences in prothrombotic phenotypes and risk of recurrent ischemic events. We have previously shown that thrombin induced whole blood TEG-G is predominantly influenced by platelet count, whereas plasma fibrin TEG-G is higher in clopidogrel responders as compared to non-responders [21]. Plasma TEG-G in our study correlated weakly with platelet count, similar to the extent previously published [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, variability in platelet derived FXIIIa may contribute to differences in prothrombotic phenotypes and risk of recurrent ischemic events. We have previously shown that thrombin induced whole blood TEG-G is predominantly influenced by platelet count, whereas plasma fibrin TEG-G is higher in clopidogrel responders as compared to non-responders [21]. Plasma TEG-G in our study correlated weakly with platelet count, similar to the extent previously published [21].…”
Section: Discussionsupporting
confidence: 90%
“…We have previously shown that thrombin induced whole blood TEG-G is predominantly influenced by platelet count, whereas plasma fibrin TEG-G is higher in clopidogrel responders as compared to non-responders [21]. Plasma TEG-G in our study correlated weakly with platelet count, similar to the extent previously published [21]. We have previously demonstrated that increased c-reactive protein in patients with coronary artery disease is associated with increased plasma TEG-G [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data point to marked differences in the extent to which selected TEG and MPA indices are influenced by warfarin and the NOACs, as are summarised in Table 5 . Some of these differences are likely to reflect whole blood versus fibrin clot formation, as it is established that platelets contribute to a fibrin clot [ 22 , 23 ], although our control group are taking at least 75 mg of aspirin daily, and this drug may also influence lysis by tPA [ 24 ]. Our data also point to marked differences between the effects of the NOACs, suggesting that dabigatran is a more effective agent than apixaban and in one respect, than rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…The MA was classified into the thrombin‐induced maximum coagulation strength (MA thrombin ), the 20 μmol/L ADP‐induced maximum coagulation strength (MA ADP ) and the fibrin‐induced maximum coagulation strength (MA Fibrin ) according to different types of activators added to the blood sample. The ADP‐induced IPA for clopidogrel was calculated by the formula: ADP‐induced IPA (%) = (MA ADP − MA Fibrin )/(MA thrombin − MA Fibrin ) . According to a previous study, the relating IPA <30% induced by 20 μmol/L ADP was defined as clopidogrel high on‐treatment platelet reactivity (HPR) .…”
Section: Methodsmentioning
confidence: 99%
“…The ADP-induced IPA for clopidogrel was calculated by the formula: ADPinduced IPA (%) = (MA ADP − MA Fibrin )/(MA thrombin − MA Fibrin ). 19 According to a previous study, the relating IPA <30% induced by 20 μmol/L ADP was defined as clopidogrel high on-treatment platelet reactivity (HPR). 20 Aspirin resistance is defined as the occurrence of more than 50% platelet aggregation after stimulation by 1 mmol/L AA as measured by TEG after aspirin therapy.…”
Section: Antiplatelet Measurementsmentioning
confidence: 99%